Technology Mediation and the Formation of a Hybrid Learning Habitus in an Acehnese Madrasah - Ifnandar, Muzni; Saifuddin, Saifuddin; Mursyidin, Mursyidin; Fauzi, Fauzi; Alwi, Alwi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Research on educational digitalization has frequently emphasized access, infrastructure, teacher readiness, and platform implementation, while paying less attention to changes in students’ learning dispositions within religious educational institutions. This study examines how digital technology mediates students’ learning habitus at MTsN 5 Pidie, a state Islamic junior secondary school in Aceh, Indonesia. It used a qualitative case study design involving five stakeholder groups: madrasah leaders, teachers, students participating in digital classes, students not yet participating in the program, and ICT staff. Data were collected through classroom observations, semi-structured interviews, and document analysis and interpreted using Bourdieu’s concepts of habitus, capital, and field. Digital tools expanded students’ access to materials and introduced new routines of information seeking, online assignment completion, and platform-based communication. These routines did not replace teacher guidance, handwritten note-taking, discipline, religious values, or adab. Instead, digital practices remained subject to teacher supervision, institutional rules, technical support, and moral expectations. Students also differed in device familiarity, platform access, account management, connectivity, and the assistance required to participate. The study interprets this pattern as a hybrid and regulated learning habitus. This case-based interpretation explains digitalization as a socially mediated institutional process rather than a straightforward transition from conventional to autonomous digital learning.